2010
DOI: 10.1002/chem.200902014
|View full text |Cite
|
Sign up to set email alerts
|

Binuclear Uranium(VI) Complexes with a “Pacman” Expanded Porphyrin: Computational Evidence for Highly Unusual Bis‐Actinyl Structures

Abstract: On the basis of uranyl complexes reacting with a polypyrrolic ligand (H(4)L), we explored structures and reaction energies of a series of new binuclear uranium(VI) complexes using relativistic density functional theory. Full geometry optimizations on [(UO(2))(2)(L)], in which two uranyl groups were initially placed into the pacman ligand cavity, led to two minimum-energy structures. These complexes with cation-cation interactions (CCI) exhibit unusual coordination modes of uranyls: one is a T-shaped (T) skelet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
49
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 44 publications
(53 citation statements)
references
References 93 publications
4
49
0
Order By: Relevance
“…Theoretical predictions on structures and reactions of the computed uranyl complexes of H4L pac and H4L provided significant support for the experimental results. [39][40][41] Additionally, these calculations, 39,40 predicted the new butterfly-like geometry for U VI 2O4 in [(OU VI (μ-O))2(L pac )] -a different type of cation-cation interaction (CCI) 32,[42][43][44][45][46][47][48][49][50][51][52][53][54][55] to that observed so far (a CCI is defined when one actinyl metal centre is coordinated by the oxo atom of a second actinyl). Here, the occupation by one oxo of a mutually cis-coordination site was explained, since a much higher energetic barrier arises from the repulsion of the second uranyl entering into the small empty pocket of [(THF)(U VI O2)(H2L pac )], as lower than the barrier to oxo migration from trans to cis-uranyl position.…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…Theoretical predictions on structures and reactions of the computed uranyl complexes of H4L pac and H4L provided significant support for the experimental results. [39][40][41] Additionally, these calculations, 39,40 predicted the new butterfly-like geometry for U VI 2O4 in [(OU VI (μ-O))2(L pac )] -a different type of cation-cation interaction (CCI) 32,[42][43][44][45][46][47][48][49][50][51][52][53][54][55] to that observed so far (a CCI is defined when one actinyl metal centre is coordinated by the oxo atom of a second actinyl). Here, the occupation by one oxo of a mutually cis-coordination site was explained, since a much higher energetic barrier arises from the repulsion of the second uranyl entering into the small empty pocket of [(THF)(U VI O2)(H2L pac )], as lower than the barrier to oxo migration from trans to cis-uranyl position.…”
Section: Introductionmentioning
confidence: 89%
“…The solvent effect of pyridine was taken into account with the Conductor-Like Screening Model, COSMO. 68,69 The Klamt radii were used for the main group atoms (H = 1.30 Å, C = 2.00 Å, N = 1.83 Å and O = 1.72 Å) 70 and for the actinide atoms (U, Np and Pu = 1.70 Å) 39,40,71,72 . The scalar relativistic ZORA method [73][74][75][76] and Slater-type TZP basis sets (labeled as B-II) were used.…”
Section: Computational Detailsmentioning
confidence: 99%
“…13 The studies of Arnold 15 and one-electron reduced uranium(V) products. 16,17 Our theoretical studies 18 showed that the H 4 L 1 ligand can accommodate two uranyl ions to form bis-uranyl complexes (UO 2 ) 2 (L 1 ). Of particular interest is the fact that the two UO 2 2+ moieties exhibit the butterfly-like and T-shaped structures as seen in Chart 2.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the aryl-linked macrocycle (H 4 L 1 ) shows energetic preference for a butterfly-like and a T-shaped bis-uranyl complex. 18…”
Section: Introductionmentioning
confidence: 99%
“…No hexavalent bis ‐uranyl counterpart has been found so far. Our previous theoretical study suggested that the penta valent uranyl bar is less rigid than the hexa valent one and more easily transformed to the cis ‐structure. Experimentally, Arnold and Love et al have chemically modified the aryl‐linked H 4 L Ar ligand and prepared an anthracenyl‐containing polypyrrolic macrocycle (H 4 L, Chart ) that has longer linker .…”
Section: Introductionmentioning
confidence: 99%